2016
DOI: 10.1111/acer.13122
|View full text |Cite
|
Sign up to set email alerts
|

Adolescent Women Induce Lower Blood Alcohol Levels Than Men in a Laboratory Alcohol Self‐Administration Experiment

Abstract: Background Adolescence is a critical period for the development of alcohol use disorders; drinking habits are rather unstable and genetic influences, such as male sex and a positive Family History of alcoholism (FH), are often masked by environmental factors such as peer pressure. Methods We investigated how sex and FH modulate alcohol use in a sample of 18-19-year-olds from the Dresden Longitudinal Study on Alcohol use in Young Adults (D-LAYA). Adolescents reported their real-life drinking in a TimeLine Fol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
17
1
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 52 publications
(56 reference statements)
2
17
1
1
Order By: Relevance
“…Our study extends these intravenous alcohol self-administration results by showing that participants with a greater percentage of biological relatives with alcohol problems were at greater risk. Our study also found higher rates of alcohol consumption in males compared to females, which is consistent with a recent study of intravenous alcohol self-administration in adolescents (9). Delay discounting has previously been observed as a predictor of laboratory alcohol consumption (8), and we confirmed that here.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Our study extends these intravenous alcohol self-administration results by showing that participants with a greater percentage of biological relatives with alcohol problems were at greater risk. Our study also found higher rates of alcohol consumption in males compared to females, which is consistent with a recent study of intravenous alcohol self-administration in adolescents (9). Delay discounting has previously been observed as a predictor of laboratory alcohol consumption (8), and we confirmed that here.…”
Section: Discussionsupporting
confidence: 93%
“…Intravenous alcohol self-administration also differs in many ways from real-world alcohol consumption. However, recent results suggest that intravenous self-administration is reflective of external consumption patterns when comparing across drinkers of varying severity (9; 39). A few individuals in our sample were in their forties and an even younger sample would have been ideal to assess the effects of these risk factors, although the vast majority of our sample (86.1%) was at or below the age of 30.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Laboratory paradigm. Participants completed an intravenous alcohol self-administration session, a paradigm which has shown good test-retest reliability and external validity in prior studies [29,30]. This paradigm eliminates the large variability in blood alcohol concentration (BAC) associated with oral alcohol intake [31,32] by bypassing gastrointestinal absorption and first-pass metabolism and using an algorithm that adjusts for age, sex, height, and weight to account for differences in alcohol distribution and elimination [33].…”
Section: Methodsmentioning
confidence: 99%
“…Intravenous self‐administration also eliminates cues such as smell, taste, and appearance, so consumption should be primarily driven by the pharmacodynamic effects of alcohol, such as dopamine release in the nucleus accumbens . This paradigm has been used to test the effects of medications on self‐administration, to show that males consume more than females, and to examine genetic effects on alcohol consumption and sensitivity . There is evidence that phenotypes elucidated in the laboratory have important clinical implications.…”
Section: Introductionmentioning
confidence: 99%